2022
DOI: 10.3390/healthcare10030516
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology and Symptomatology of Drooling in Parkinson’s Disease

Abstract: Drooling can present in patients with Parkinson’s disease (PD), and it is manifested as an excessive pooling of saliva inside the oral cavity. Currently, the exact pathophysiological mechanism of drooling in PD is not yet fully explicated. Thus, it becomes crucial to understand if some clinical characteristics may emphasize drooling or if they are just concomitant. In PD, excessive drooling has been associated with a higher burden of non-motor symptoms, such as cognitive impairment, sleep problems, autonomic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
(162 reference statements)
0
2
0
Order By: Relevance
“…Sialorrhea was originally regarded as a parkinsonian symptom resulting from the decreased motility of the esophagus due to bradykinesia of the laryngeal muscle in the era of first‐generation antipsychotics (Srivanitchapoom et al., 2014). Recent reviews have shown that the exact pathophysiological mechanism for developing sialorrhea in Parkinson's disease is not yet fully understood; it is likely not due to a single factor that is limited to the nigrostriatal dopamine pathway, but rather to a mixture of factors (Polychronis et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Sialorrhea was originally regarded as a parkinsonian symptom resulting from the decreased motility of the esophagus due to bradykinesia of the laryngeal muscle in the era of first‐generation antipsychotics (Srivanitchapoom et al., 2014). Recent reviews have shown that the exact pathophysiological mechanism for developing sialorrhea in Parkinson's disease is not yet fully understood; it is likely not due to a single factor that is limited to the nigrostriatal dopamine pathway, but rather to a mixture of factors (Polychronis et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…We initially thought that Parkinson's patients had excessive salivary production, but studies have found that Parkinson's patients have less salivary production than normal people [28][29][30]. Sialorrhea can be caused by excessive salivation, di culty swallowing, or both [29,31]. Some studies have shown that sialorrhea is thought to be due to dysphagia that reduces the effective removal of saliva rather than excessive drooling [32].…”
Section: Introductionmentioning
confidence: 99%
“…In a review article, Polychronis et al critically approached the relevant literature of drooling in patients with Parkinson's disease (PD), and the possible relationship between excessive drooling and other clinical manifestations of PD, such as cognitive impairment, sleep difficulties, autonomic dysfunction, constipation, and orthostatic hypotension [15]. The study concluded that excessive drooling in PD patients is due to a wide range of factors.…”
mentioning
confidence: 99%